Riesgo de presentar enfermedades cardiometabólicas según indicadores antropométricos en el personal médico y de enfermería del Hospital General Julius Doepfner - Vargas Vargas, Stefany Margoth (2022)
Cardiometabolic diseases are a problem of interest in public health because they occupy the first places in terms of morbidity and mortality in the population, studies reveal that the same occurs in health personnel; approaching this problem from a perspective of prevention and early detection of the risk of developing them, allows us to have an advantage over the predominant curative model; the increase in body fat and its distribution represents an important risk factor for the development of these diseases; the indicators, body mass index and abdominal circumference allow this risk to be stratified early and intervention measures to be implemented. In this context, the research proposed as a general objective to analyze the risk of presenting cardiometabolic diseases according to anthropometric indicators in the medical and nursing staff of the Julius Doepfner General Hospital and as specific objectives, to describe the demographic data of the medical and nursing staff, to estimate the risk of presenting cardiometabolic diseases according to the anthropometric indicators of body mass index and abdominal circumference in the medical and nursing staff of the Julius Doepfner General Hospital and to propose health prevention actions to reduce the risk of presenting cardiometabolic diseases. This is a cross-sectional descriptive quantitative approach study that included 107 professionals, 63 physicians and 44 nurses, who, after performing anthropometric measurements, were established a risk of presenting cardiometabolic diseases, obtaining as main results that, according to the body mass index indicator, 45.8% of the personnel had a moderate risk, followed by low risk with 34.6% of presenting cardiometabolic diseases and, according to abdominal circumference, the highest percentage was placed in the high and very high risk categories with 37.4% and 31.8% respectively